2002
DOI: 10.2136/vzj2002.1720
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hydraulic Nonequilibrium on Pressure Plate Data

Abstract: Pressure plates are used routinely to measure water‐retention characteristics of soils. Plates of varying porosity are used, depending on the pressure range of interest. For applied pressures up to 1.5 MPa, 15‐bar porous ceramic plates with fine porosity are used because of their high bubbling pressure (>1.5 MPa), which limits airflow through the plate. The typical saturated hydraulic conductivity of the 15‐bar plate is <3 × 10−11 m s−1 Low plate conductance coupled with decreasing soil hydraulic conductivitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…The point for log P a = 4.2 shows that this soil is not in thermodynamic equilibrium because it is above the GG curve. This effect appears to be the same as that which was described as a problem by Bittelli andFlury (2009), Cresswell et al (2008) and Gee et al (2002).…”
Section: Comparison Of Experimental Results and Ggsupporting
confidence: 78%
See 3 more Smart Citations
“…The point for log P a = 4.2 shows that this soil is not in thermodynamic equilibrium because it is above the GG curve. This effect appears to be the same as that which was described as a problem by Bittelli andFlury (2009), Cresswell et al (2008) and Gee et al (2002).…”
Section: Comparison Of Experimental Results and Ggsupporting
confidence: 78%
“…In particular, the use of the pressure cell apparatus, usually using porous ceramic plates (but sometimes membranes), has been found to be problematic. At high cell pressures, corresponding to low values of water potential or large values of pore water suction, it has been found that the water in the soil samples does not equilibrate with the air pressure in the cell as expected (Bittelli and Flury, 2009;Cresswell et al, 2008;Gee et al, 2002). In these cases, the expected water potential was the cell pressure and the value of potential reached was measured by psychrometry.…”
Section: Problems Associated With Water Retention Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…The ASTM D-6836-02 standard establishes that the equilibrium time should be monitored according to the level of suction and states that for suction less than 500 kPa it is considered equilibrated the system that does not drain any water for at least 24 h, for suction between 500 and 1,000 kPa this time should be 48 h and for suction greater than 1,000 kPa no water should be drained for at least 96 h. Many authors monitored the equilibrium time behaviour, some of them reporting that the equilibrium is not reached (e.g. Gee et al 2002) and others reporting that the equilibrium is reached (e.g. Leong et al 2004).…”
Section: Equilibrium Timementioning
confidence: 99%